Incontinence surgery in obese women: comparative analysis of short- and long-term outcomes with a transobturator sling. Issue 2 (February 2016) - Pereira, Inês; Valentim-Lourenço, Alexandre; Castro, Catarina; Martins, Inês; Henriques, Alexandra; Ribeirinho, Ana
Abstract Introduction and hypothesis Midurethral slings (MUS) are still discussed in complex incontinence situations, such as obesity, lacking sustained efficacy validation in this particular sub-population. We hypothesized that the outcomes of a transobturator MUS, such as TVT-O, do not differ according to body mass index (BMI) over a 4-year period. Methods We conducted a retrospective analysis of 281 women who underwent TVT-O at our institution, between 2004 and 2012. Patients were stratified into obese (BMI ≥ 30 kg/m2 ) or non-obese (BMI < 30 kg/m2 ). We compared preoperative and postoperative parameters, including objective cure (negative stress test), complications, and quality of life scores. Data were collected at 0, 6, 12, 24, and 48 months. We used Fisher's exact test for categorical variables and Student'st test or the Mann–WhitneyU test for continuous variables. Results Baseline characteristics of the obese (n  = 122) and non-obese groups (n  = 159) were similar. We found no significant differences between groups in terms of objective cure rates at all follow-up evaluations, with 95.8 % and 95 % at 48 months in the non-obese and obese groups respectively. There were no significant differences in the cumulative complication rates of both groups. Quality of life assessment also showed no significant differences between groups at all follow-up visits. At 48 months our follow-up rate was 59 % (n  = 96) and 60.4 % (n  = 72) in the non-obese and obese group respectively (p  = 0.9). Conclusions The TVT-O procedure is effective and safe in the long term for stress incontinence treatment, regardless of BMI.